Reinhold Schneider und der Nationalsozialismus - Nowak, Roman (Studia Germanica Posnaniensia, 2018)
This article is an attempt at the presentation of the writer's silhouette in the period 1933-1945 against the background of the then historiosophic, philosophic, ideological and political conceptions. At the same time it is an outline of the writer's way to the conservatively conditioned concept of ,,forms of life" to the conception of "the conscience of time", from the idea of ruthless fight for the perfectness of the form of state to the active opposition of its attitude in the Third Reich.